Effect of heat stress on performance and expression of selected amino acid and glucose transporters, HSP90, leptin and ghrelin in growing pigs. (July 2016) - Cervantes, Miguel; Cota, Margarita; Arce, Néstor; Castillo, Gilberto; Avelar, Ernesto; Espinoza, Salvador; Morales, Adriana
Abstract: Exposing animals to high ambient temperature provokes heat stress (HS) that may affect cellular function and reduced productive performance. The effect of chronic exposure (21d) of pigs to high ambient temperature on expression of amino acid (b 0, + AT, CAT1) and glucose (SGLT1, GLUT4) transporters, ghrelin, leptin and HSP90 was evaluated. Eighteen pigs (32.6 kg body weight) were distributed into 3 groups: (1) pigs housed under natural high ambient temperature conditions, and fed ad libitum (HS); (2) pigs housed in an air-conditioned room at 24 °C (thermo-neutral) fed ad libitum (TNad ); (3) pigs housed as in (2), but pair-fed with the HS pigs (TNpf ). Body temperature, respiratory frequency, weight gain, feed intake, and feed conversion ratio were measured. At d-21 pigs were euthanized and samples from stomach, duodenum, jejunum, liver, longissimus and semitendinosus muscles, and white adipose tissue were collected for mRNA analysis. In the HS room ambient temperature fluctuated every day (23.6–37.6 °C). Respiratory frequency and body temperature were higher in HS pigs ( P <0.001). Weight gain and feed intake of TNad were higher ( P <0.001) than TNpf and HS; gain: feed ratio was not affected by ambient temperature. Expression of HSP90 was higher in duodenum and longissimus ( P ≤0.038) of HS compared to TNpf . Expression of ghrelin, leptin and b 0, + AT were not affected by ambient temperature ( P >0.050). CAT1 expression in liver was higher ( P =0.050) but in longissimus was lower ( P =0.017) in HS than in TNpf pigs. Expression of SGLT1 was higher ( P =0.045) in duodenum of HS than in TNpf but it was not different in jejunum ( P =0.545); GLUT4 tended to be higher in liver and semitendinosus of HS pigs ( P =0.063). In conclusion, feed intake remains low whereas respiratory frequency and body temperature remain higher; and expression of HSP90, CAT1, SGLT1 and GLUT4 increases in some tissues in pigs under chronic HS conditions. Highlights: Pigs are less productive when are exposed to heat stress (HS). HS pigs cannot maintain their normal respiratory frequency and body temperature. HS pigs increased expression of HSP90 and nutrient transporters in some tissues. These alterations seem to be part of adaptive mechanisms to chronic HS.